2010
DOI: 10.1089/pho.2009.2697
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Resin Cement to Yttrium-Stabilized Tetragonal Zirconia Ceramic Treated with Air Abrasion, Silica Coating, and Laser Irradiation

Abstract: Although air abrasion and silica coating were the most effective surface treatment methods, CO(2) and Er:YAG laser irradiation alone or Nd:YAG laser irradiation after air abrasion may be used as an alternative treatment method to increase the bond strength between resin cement and Y-TZP material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
185
1
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(235 citation statements)
references
References 30 publications
21
185
1
17
Order By: Relevance
“…A rough surface increases the surface area, improves wettability by reducing surface tension, and creates micromechanical retention. Al 2O3 air abrasion is one of the common methods used to increase surface roughness 8,19,32,33) . Some investigators suggested that superior bonding to zirconia was obtained when with airabraded surfaces [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…A rough surface increases the surface area, improves wettability by reducing surface tension, and creates micromechanical retention. Al 2O3 air abrasion is one of the common methods used to increase surface roughness 8,19,32,33) . Some investigators suggested that superior bonding to zirconia was obtained when with airabraded surfaces [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in temperature and surface destruction due to laser absorption by ceramic creates some porosity on the surface, inducing an augmentation of micromechanical retention. 36 The evaluation by SEM revealed the presence of microscratches and very shallow grooves that are less aggressive than the ones observed in the ROC-treated specimens. Worthy to mention is that the intensity of the laser treatment is an important factor in the treatment outcome.…”
Section: Discussionmentioning
confidence: 87%
“…However, Zirconia ceramics are densely sintered mechanically tough materials, which might be difficult to be coated by silica. Research studies showed that the tribochemical silicacoating/silanation had the same or similar effects as regular air-abrasion with alumina particles on improving zirconia-resin bond strengths, indicating tribochemical silica-coating provided only air-abrasion effect for creating surface roughness (Akyil et al, 2010;Re et al, 2008;Tanaka et al, 2008;Smith et al, 2011). It was reported that tribochemical silica-coating didn't provide stable resin-Zirconia bond strength (Kern and Wegner, 1998).…”
Section: Non-silica-based Zirconia Ceramicsmentioning
confidence: 99%